Effects of a One-Time Organic Fertilizer Application on Long-Term Crop and Residue Yields, and Soil Quality Measurements Using Biointensive Agriculture - Beeby, John; Moore, Steve; Taylor, Laura; Nderitu, Samuel (Frontiers in Sustainable Food Systems, 2020)
Abstract Background: Closing the yield gap, especially in Africa, using environmentally appropriate and sustainable methods is important to meet current and future food demands. Grow Biointensive Sustainable Agriculture (GBSA) is an organic method that combines eight sustainable practices that may close the yield gap, increase food production, improve soil quality and reduce soil nutrient loss. Method: Utilizing the GBSA method, four Kenyan farms over four years tested the effect of a one-time application of organic fertilizers (recommended based on soil testing) on crop and residue yields and soil parameter levels. Results: Yearly crop edible yields increased overall for maize, sorghum and sweet potatoes. Amaranth showed no significant change. Yearly crop residue yields increased for sweet potatoes, and increased marginally for amaranth, maize, and sorghum. Harvesting practice changes in cowpeas and lablab made interpretation more complex, but both edible and residue yields for these crops varied from unchanged to significantly increased. Fourteen soil parameters were tested. Boron, electrical conductivity, magnesium, organic matter, phosphorus, potassium, sulfur and zinc increased significantly. Calcium, copper, iron, pH, and sodium showed no significant changes, and only manganese levels decreased significantly. Conclusion: Combining a single application of recommended organic fertilizers and the GBSA method, farmers may be able to improve their crop yields and maintain soil fertility in a manner that is more sustainable.